Risk Mitigation Effects for Mudhārabah Financing Accounting Treatment (Case Study at Bank “YIX” in Aceh) - Muslina Muslina; Angga Syahputra (Fakultas Ekonomi dan Bisnis Islam Institut Agama Islam Negeri Palangka Raya, 2021)
Mudharabah financing has a high level of risk caused by moral hazard and adverse selection. The existence of these two risks resulted in a simultaneous impact on the reputation and liquidity of the bank “YIX”, thus requiring risk mitigation. On the other hand, the risk mitigation action raises the contradiction of PSAK No. 105 in particular the recognition of financing, profit sharing and expenses. This study was conducted qualitatively by observing the phenomenon at the bank